Conceptual Model to Identify Technological Synergic Relationships of Strategic Level in a Medium-Sized Chilean Port - Duran-San Martin, C (Elsevier B.V., 2016)
The present study focuses on a medium-sized Chilean port to analyze a mixed network composed of private/public actors, permanently linked to an uncertain strategic ambience. Their linkage to an uncertain macro-ambience is complex which may present degrees of synergy with those strategies dealing with political, economic, social, technological and environmental aspects (PESTE). Later, this research identifies the strategic ambience of the Port Community and its synergic links with the other actors who compose the mixed network. Taking into account each actor s strategic statements, it is possible to infer that each public organization and private enterprise elaborates its strategies individually, dismissing joint collaboration as a factor to improve efficiency and effectiveness in their port activities. In the proposed conceptual model design, each actor s innovation strategies are linked to the corresponding technological synergic effect (TSE). With the diagnosis of the strategic ambience of the Community, it is possible to transform the strategies used by the mixed network into technological strategic descriptors. Finally, the technological strategic statements expressed by the Community are conceptually evaluated and compared to existing strategic and innovation actions followed by the members of the Port Community. © 2016 The Author(s).